Analisis Pengaruh Kualitas Produk, Harga, Kualitas Pelayanan Terhadap Keputusan Pembelian ( Studi Pada Konsumen Kafe Om. Kopi Di Kota Malang ) - Mayantya Dianingtyas; Agus Widarko; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe research a purpose to knowing and analyze Product Quality, Price, and Service Quality to Purchasing Decisions on consumers cafes Om.Kopi in Malang city both partially and simultaneously. This research uses Explanatory Research with a quantitative approach. The population in this research consumers both coming directly and indirectly at the café Om.Kopi Malang city. Samples taken as many as 94 respondents. The sampling technique used was Purposive Sampling. Data were analyzed using multiple linear regression analysis processed with SPSS 16.0 software. Data collection methods used were questionnaire and interview. The results showed that the Quality of the Products effect has an significant partially to Purchasing Decisions. Meanwhile, Price and Service Quality has an effect, but insignificant partially on Purchasing Decisions. And, Product Quality, Price, and Service Quality has an effect significant simultaneous to Purchasing Decisions. Keywords: Product Quality, Price, Service Quality, and Purchasing Decisions